EFEKTIVITAS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN PADA PEMBELAJARAN GEOGRAFI DI SMAN 1 RASAU JAYA - Anggraini, Tanti; Ulfah, Maria; Sugiarto, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine the effectiveness of using instructional video media in improving student learning outcomes. This type of research is experimental research with a quasi-experimental form. The data was collected by giving a test, in the form of a multiple choice written test, totaling 50 questions to the students of class XI IPS 2 as the experimental class and class XI IPS 3 as the control class of SMAN 1 Rasau Jaya. Based on the results of the average post-test score of the experimental class of 62.83, while the post-test score of the control class was 53.66. From this data, it can be seen that there are differences in student learning outcomes in the experimental class and the control class. Judging from the different test results with tcount table (3.074 2.048) with a value of 0.003 0.05, which means that there are differences in student learning outcomes. This shows that the effectiveness of using video media can improve student learning outcomes. This is also evidenced by the result of an effect size of 0.8 with criteria classified as high.Keywords: Effectiveness, Video Media, Learning Outcomes